Determination of CRP blood level in type 1 diabetic patients and the effect of aerobic and resistance training on the level of this biomarker - Yousef Moghaddasi Kouchaksaraei; Farshad Ghazalian; Saeid Abediankenari; Khosro Ebrahim; Hossein Abednatanzi (Babol University of Medical Sciences, 2022)
Background: Increasing prevalence of diabetes and its complications, including cardiovascular problems, increase the cost of health care. With proper planning to change lifestyle, like costs and complications of type 1 diabetes could be diminished. The present study investigated the effect of aerobic and resistance training on blood CRP level of type 1 diabetic patients as a protective marker on cardiovascular cells. Methods: In this descriptive cross-sectional study, 32 patients with type 1 diabetes were divided into two groups of aerobic and resistance exercise training. Serum CRP levels were measured in all patients before and after exercise. Data were analyzed using Mann-Whitney, Bootstrap and SPSS tests. Results: In this study, for abnormal data, Bootstrap method was used, which created an acceptable confidence interval. And using analysis of variance to control the effect of CRP (interfering) level before and after exercise was not significant (P=0.37). Conclusion: Considering the relationship between exercise training with CRP level in type 1 diabetic patients specially in aerobic training group as well as CRP level according to the training program condition, it can be concluded that there is not effective relationship between this biomarker and exercise training in type 1 diabetic patients.